THE ROLE OF VILLAGE VOLUNTEERS IN RESPONDING TO COVID-19 IN THE LEVEL OF TRUST OF THE VILLAGE COMMUNITIES ABOUT COVID-19 IN DEWANTARA DISTRICT NORTH ACEH REGENCY IN 2021 - Musdarianto, Musdarianto; Andala, Sri (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Covid-19 Respons Village Volunteers were formed based on a circular letter from the Ministry of Villages and Development of Disadvantaged Regions as stated in SE Number 8 of 2020 concerning Covid-19 Respons Villages and Affirmations of Village Cash Work with the tasks of conducting outreach and prevention of Covid-19 by providing communication, information and education to the public about Covid-19. This study aims to determine the role of village volunteers responding to Covid-19 in the level of trust of the village community about Covid-19 in Dewantara District, North Aceh Regency. Methods: The type of research used is quantitative and data presentation is done descriptively. The research sample is 397 respondents. Results: The results showed that the characteristics of the respondent's were based on the age of the majority 26-35 years (38.3%), the sex of the majority was male (61%), the education of the majority was high school (53.7%) and the occupations of the majority were housewives (22.9%). The majority of the communication role of the Covid -19 response village volunteers was good (66.8%), the majority of information role was not good (52.9%) and the majority of education roles was not good (71.5%). The village community's level of trust about Covid -19 is mostly in the doubtful category (45.6%) and the lowest is in the very trust category (1%). Recommendation: Based on the results of the study, it is suggested to Covid-19 Response village volunteers to increase the role of communication, information and education to the public about Covid-19, and to the public to be able to find reliable reference sources about Covid-19, and to increase confidence in Covid-19.